2021
DOI: 10.3390/nu13030836
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia, a Possible Microbial Marker for Poor Glycemic Control in Qataris Children Consuming Arabic Diet—A Pilot Study on Pediatric T1DM in Qatar

Abstract: In Qatar, Type 1 Diabetes mellitus (T1DM) is one of the most prevalent disorders. This study aimed to explore the gut microbiome’s relation to the continuous subcutaneous insulin infusion (CSII) therapy, dietary habits, and the HbA1c level in the pediatric T1DM subjects in Qatar. We recruited 28 T1DM subjects with an average age of 10.5 ± 3.53 years. The stool sample was used to measure microbial composition by 16s rDNA sequencing method. The results have revealed that the subjects who had undergone CSII thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
(46 reference statements)
0
6
1
Order By: Relevance
“…On the contrary, few studies have reported a higher level of A. muciniphila during disease progression [ 78 , 79 ]. In our previous two studies, we found that a higher abundance of A. muciniphila was linked with the activation of LPS in CKD mice than in the control mice [ 80 ], and insufficient glycemic control in pediatric subjects with T1DM is linked to the higher level of A. muciniphila [ 81 ]. Thus, the level of A. muciniphila is critical for the pathophysiology of certain diseases where there is activation of an inflammatory-mediated pathway.…”
Section: Mechanisms Of Gut Microbiota-mediated Htnmentioning
confidence: 99%
“…On the contrary, few studies have reported a higher level of A. muciniphila during disease progression [ 78 , 79 ]. In our previous two studies, we found that a higher abundance of A. muciniphila was linked with the activation of LPS in CKD mice than in the control mice [ 80 ], and insufficient glycemic control in pediatric subjects with T1DM is linked to the higher level of A. muciniphila [ 81 ]. Thus, the level of A. muciniphila is critical for the pathophysiology of certain diseases where there is activation of an inflammatory-mediated pathway.…”
Section: Mechanisms Of Gut Microbiota-mediated Htnmentioning
confidence: 99%
“…1 The International Diabetes Federation (IDF) Diabetes Atlas reported that the incidence of T1DM continues to increase worldwide, with approximately one million cases presented annually. 1,2 T1DM had many complications including severe hypoglycaemia, ketoacidosis, diabetic retinopathy, nephropathy and cardiovascular complications. 3 Currently, the main treatment for T1DM patients was insulin replacement therapy.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM), caused by the autoimmune destruction of pancreatic beta cells, was a metabolic disorder, and it could result in insulin deficiency, which affect all age groups irrespective of gender 1 . The International Diabetes Federation (IDF) Diabetes Atlas reported that the incidence of T1DM continues to increase worldwide, with approximately one million cases presented annually 1,2 . T1DM had many complications including severe hypoglycaemia, ketoacidosis, diabetic retinopathy, nephropathy and cardiovascular complications 3 .…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…Prior studies have highlighted the benefits of protocols involving prebiotics such as FOS (Everard et al., 2013 ), GOS (Lakshmanan et al., 2021 ), β‐glucans (Arena et al., 2017 ), and mineral supplementation comprising magnesium (Santos‐Marcos et al., 2019 ), zinc (Shen et al., 2019 ), and selenium (Kumar et al., 2020 ), alongside plant‐derived compounds like flavonolignans (silymarin) (Xu et al., 2022 ). These protocols have exhibited advantages in ameliorating the pathogenesis of various noncommunicable chronic illnesses, such as obesity and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%